2011
DOI: 10.4317/jced.3.e5
|View full text |Cite
|
Sign up to set email alerts
|

Bone height measurement of maxillary and mandibular bones in panoramic radiographs of edentulous patients

Abstract: Objectives. The purpose of this in vitro study were to determine variation in maxillary and mandibular vertical measurements and to assess vertical bone loss made from panoramic radiographs in edentulous measurements. Study Design. In this descriptive study, a total of 600 panoramic radiograph's of edentulous patient were examined. The mean ages of edentulous patients were 31 and 87 years respectively. Measurements were made from reference lines drawn from anatomic landmarks on standardized panoramic rediograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
4
14
0
3
Order By: Relevance
“…Another previous study coincides with this result which observed the reduction was more pronounced in males than in females [20]. Otherwise, another studies reported the reduction was significantly more in females than males [13,21].…”
Section: Discussionsupporting
confidence: 81%
“…Another previous study coincides with this result which observed the reduction was more pronounced in males than in females [20]. Otherwise, another studies reported the reduction was significantly more in females than males [13,21].…”
Section: Discussionsupporting
confidence: 81%
“…[25] Changes regarding the maxillary arch are not the concern of this review .however; it should be given a great concern as the unfavorable distribution of forces of restoration may contribute in the upper arch changes. [3,9,26] panoramic radiographs have been reported to be sufficiently reliable to evaluate the available bone height in the area of posterior mandible. [27][28][29] In this review measuring of the bone height changes was done using the proportional method introduced by Wilding et al [30] The author considered the changes of the proportional area measurement could represent the changes of the alveolar ridge height.…”
Section: Discussionmentioning
confidence: 99%
“…However, rather frequently, removable dentures are inserted immediately after tooth extraction to preserve esthetics, speech, and jaw relation, as well as to protect the alveolar coagulum. The U-shaped profiles in this study with side walls up to 90 • angulation simulated the geometry of well-preserved alveolar ridges as they might be expected when extracting broken down teeth [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The intaglio U-shaped profiles corresponded in their dimensions to average sized alveolar ridges [16,17] with the purpose of simulating the shape of intaglio removable denture surfaces. All cubes were made from PMMA (Palapress, Heraeus-Kulzer, Hanau, Germany) according to manufacturer's instructions (powder to liquid ratio 10 g to 7 mL, mixing time 15 s at 23 • C).…”
Section: Methodsmentioning
confidence: 99%